Microbiological indices of unregulated herbal drinks in Benin City, Nigeria: A potential health hazard to consumers - Zainab Omoruyi; Moses Ikpomwonsa Okundaye; Tunde Oluwasegun Egunjobi (Environmental Disease, 2024)
Background: The use of herbal medicine has increased globally due to people's dissatisfaction with conventional medicine, family traditions, poverty, and prior positive experiences. Since the last decade, the general public has become increasingly interested in herbal products from several medicinal plants. This study sought to evaluate the microbial contamination of liquid herbal drinks sold in Benin City, Nigeria. Materials and Methods: Fifty different herbal medicines were purchased from three different locations in the study area. The 50 herbal medicines were centrifuged and the sediment was used for culture, biochemical, and antibiotic tests for the identification of isolated microorganisms and the assessment of the total viable bacterial count. Results: In comparison to regulated herbal preparations (4%), a percentage (36%) of unregulated herbal preparations contained viable bacteria. The most common bacterium found in unlicensed herbal medicines was Klebsiella pneumonia (10%). The percentage of regulated and unregulated herbal preparations that had microbiological contamination that was above the permissible limit (>10 colony-forming unit/ml) was 2% and 26%, respectively. Conclusions: Numerous unlicensed herbal treatments in Benin City have microbial contamination over the World Health Organization-permitted limit for aerobic and coliform bacteria. The regulatory bodies should step up their efforts to make sure that all herbal medicines marketed in the nation are legally registered and created in compliance with current Good Manufacturing Practice standards.